オトガイ下部に下顎骨露出を伴い治療に難渋した両側陳旧性顎関節脱臼の1例 - 桐田, 忠昭; 高嶌, 森彦; 川上, 哲司; 稲掛, 耕太郎; 井上, 智裕; 今井, 裕一郎 (日本口腔外科学会雑誌, 2013)
We report a case of long-standing bilateral anterior dislocation of the temporomandibular joint (TMJ) with mandibular bone exposure at the submental region. A 83-year-old woman was referred to our department for further evaluation and treatment of bilateral anterior dislocation of the TMJs. Clinical and radiographic examinations showed bilateral anterior dislocation of the TMJs, and the patient was treated by manual repositioning of both TMJs, However, the treatment result was incomplete. Then, open reduction by a preauricular temporal approach was performed with the patient under general anesthesia. Finally, a Dautrey procedure with Piezosurgery®, joint arthroplasty, eminoplasty of the TMJ, and transplantation of a double pedicle flap for a decubitus ulcer in the submental region were performed. Since dislocation recurred after surgery, maxilomandibular fixation was needed. The postoperative course was good, and no recurrence has occurred as of 9 months after operation.